2006
DOI: 10.1017/s1041610205002991
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric psychiatry consultations in a Turkish university hospital

Abstract: Turkish geriatric psychiatry consultation patients display similar characteristics to elderly patients from other western countries. The main difference comes from diagnosis of adjustment disorder, which may be related to hospital conditions and strong family ties in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…High referral rates for mood disorder (28%), similar to previous studies which reported a higher rate of referrals to both liaison services in general (25.9%; [8]) and liaison psychogeriatric services (18.4%–30%; [9, 10]).…”
Section: Discussionsupporting
confidence: 86%
“…High referral rates for mood disorder (28%), similar to previous studies which reported a higher rate of referrals to both liaison services in general (25.9%; [8]) and liaison psychogeriatric services (18.4%–30%; [9, 10]).…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of depression in patients with CHF is high, ranging from 24% to 42%. [2] Depression has been shown to be significantly associated with a declined function, increased hospital readmission, and higher mortality rates in people with CHF. [2] In addition, CHF risk is increased by depression [2] , specifically in those previously at risk for CHF such as systolic hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Depression has been shown to be significantly associated with a declined function, increased hospital readmission, and higher mortality rates in people with CHF. [2] In addition, CHF risk is increased by depression [2] , specifically in those previously at risk for CHF such as systolic hypertension. [3] A recent study has examined the medical records of 7719 CHD patients, in which depression was found to be related to an increased risk of CHF.…”
Section: Introductionmentioning
confidence: 99%
“…It was diagnosed in 31.3% of elderly inpatients who received a psychiatric consultation (22). An AD might be the result of losing a spouse or close kin, physical illnesses, retirement, or financial problems.…”
Section: Discussionmentioning
confidence: 99%